Co-Occurrence of Cystic and Alveolar Echinococcosis in the Liver: A Case Report - WANG, Qiang (Iran J Parasitol, 2021)
Morbidity of mixed cystic and alveolar echinococcosis (CE and AE) is exceptionally rare. Less literature retrieved from a database on the internet detailed the content, including radiography, pathology, and therapeutics data. Such a case of co-occurrence of the different Echinococcus species was diagnosed and treated at our hospital center from Nov 2019 to Feb 2020. A 30 yr old female from the pastoral area in Qinghai Province, China, was diagnosed with a case of echinococcosis and diagnosis was confirmed after image studies, immunoassaying of hydatid enzymes, life history and pathology result. The patient underwent hepatectomy along with excision of the internal capsule. Post-operative pathology was done, and it confirmed a mixed infection of both CE and AE. The patient recovered well without complications after liver-protecting and tissue repair treatment for 15 days. Knowing about infective mode and immune method of the case might be vital for research on variation for Echinococcus infection.